Kinetics of neuropeptide Y, catecholamines, and physiological responses during moderate and heavy intensity exercises. (April 2022) - Eugster, Philippe J.; Bourdillon, Nicolas; Vocat, Céline; Wuerzner, Gregoire; Nguyen, Toan; Millet, Grégoire P.; Grouzmann, Eric
Abstract: Neuropeptide Y 1–36 (NPY1–36) is a vasoconstrictor peptide co-secreted with norepinephrine (NE) by nerve endings during sympathetic activation. NPY1–36 potentiates NE action post-synaptically through the stimulation of the Y1 receptor, whereas its metabolite NPY3–36 resulting from DPP4 action activates Y2 presynaptic receptors, inhibiting NE and acetylcholine secretion. The secretions of NPY1–36 and NPY3–36 in response to sympathetic nervous system activation have not been studied due to the lack of analytical techniques available to distinguish them. We determined in healthy volunteers NPY1–36, NPY3–36 and catecholamine kinetics and how these neurotransmitters modulate the physiological stress response during and after moderate- and heavy-intensity exercises. Six healthy males participated in this randomized, double-blind, saxagliptin vs placebo crossover study. The volunteers performed an orthostatic test, a 30-min exercise at moderate intensity and a 15-min exercise at heavy intensity each followed by 50 min of recovery in two separate sessions with saxagliptin or placebo. Oxygen consumption (V̇O2 ), ventilation and heart rate were continuously recorded. NE, epinephrine, NPY1–36 and NPY3–36 were quantified by tandem mass spectrometry. We found that exercise triggers NPY1–36 and NE secretion in an intensity-dependent manner and that NE returns faster to the baseline concentration than NPY1–36 after exercise. NPY3–36 rises during recovery parallel to the decline of NPY1–36. Saxagliptin reverses the NPY1–36/NPY3–36 ratio but does not affect hemodynamics, nor NPY1–36 and catecholamine concentrations. We found that NPY1–36 half-life is considerably shorter than previously established with immunoassays. NPY1–36 and NE secretions are finely regulated to prevent an excessive physiological Y1 stimulating response to submaximal exercise. Highlights: The kinetics of neuropeptide Y and its fragments during exercise was described Exercise intensity increases circulating neuropeptide Y and its DPP4 metabolite Neuropeptide Y does not potentiate cardiovascular performance Saxagliptin intake does not modify kinetics of V̇ 5 O2, ventilation, nor heart rate The mechanism of regulation of neuropeptide Y during exercise is unknown